Język i transmisja kulturowa w tatarskich kitabach. Stan badań - Kulwicka-Kamińska, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article discusses the kitab studies covering the physical and cultural legacy of the Tatars of the former Grand Duchy of Lithuania (today: Polish, Belarusian and Lithuanian Tatars). Religious manuscripts, including kitabs, are a part of Tatars’ cultural legacy, hence the article presents these writings and the areas of research on kitabs that cover: a) cataloguing the manuscripts; b) monographic studies providing their philological analysis; c) discussion of their content, with attention to Muslim and Christian traditions; d) textual analysis of these old texts; e) editorial preparations.